2016
DOI: 10.3329/bmj.v45i2.28973
|View full text |Cite
|
Sign up to set email alerts
|

Attitude and practice of cervical cancer screening among the female doctors of Bangabandhu Sheikh Mujib Medical University

Abstract: Cervical cancer is the most common cancer in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
(8 reference statements)
2
8
1
Order By: Relevance
“…This is also the most commonly cited reason in other countries such as Turkey, Bangladesh, Gabon and Korea. [26][27][28][29] Therefore, increasing awareness of and education about cervical cancer screening is necessary and independent of the modality of screening. While selfswabs and other self-sampling devices have been examined and reported to be reliable 6 and not inferior to specimens obtained by physicians, 30 it is necessary to investigate the perception and acceptability of selfsampling among multiethnic Malaysian women, especially potential users who have never undergone Pap testing.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the most commonly cited reason in other countries such as Turkey, Bangladesh, Gabon and Korea. [26][27][28][29] Therefore, increasing awareness of and education about cervical cancer screening is necessary and independent of the modality of screening. While selfswabs and other self-sampling devices have been examined and reported to be reliable 6 and not inferior to specimens obtained by physicians, 30 it is necessary to investigate the perception and acceptability of selfsampling among multiethnic Malaysian women, especially potential users who have never undergone Pap testing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, health education programs should empower women in relation to the Papanicolaou test, not only for the increase of knowledge, but also in order to bring about positive change in the attitude of the women toward the examination. 15 The findings show that, for the participants, the examination was performed with the aim of detecting sexually transmitted infections, revealing distorted information concerning the Papanicolaou test itself, as well as the modes of transmission and prevention; unlike the findings of another study 11 in which 85% of the women identified the examination as a procedure for the detection of the precursor lesions of cervical cancer, enabling an early diagnosis.…”
mentioning
confidence: 52%
“…This could be probably explained by the differences in the education status, social behavior, media exposure and health facilities available among the study population. [10][11][12][13][14][15][16][17] When asked about cervical cancer screening, only 8.1% were aware of Pap smear test. This was slightly better than the awareness about screening reported (6.5%) by study done in Lucknow.…”
Section: Resultsmentioning
confidence: 99%